Cytotoxic Activity Against L1210 Leukemia Cells from the Ethyl Acetate Fraction of Kenikir Leaves (Cosmos. Caudatus) Preserved by Gamma Irradiation - Susanto Susanto; Ermin Katrin Winarno; Hendig Winarno (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Kenikir leaves (Cosmos caudatus) Has been used as traditional medicine, especially as an anti-cancer, this plant has been in Indonesia both in herbs and capsules. Microbial contamination of herbal medicinal raw materials occurs when the storage process is done. One of the preservation techniques used in the industry is using gamma irradiation techniques to reduce microbial and fungal contamination. The purpose of this research was to study the effect of gamma irradiation for the preservation of kenikir leaves (C. caudatus) as an anti-cancer based on cytotoxic activity using L1210 leukaemia cells. The simplicia was gamma-irradiated by Co-60 source with variation doses of 0 (control); 5; 7.5; 10; and 15 kGy. Then the irradiated and control samples were macerated successively using n-hexane, ethyl acetate, and ethanol. The active extract (ethyl acetate) was further fractionated using column chromatography, obtained seven fractions (F1 - F7). The seven fractions' cytotoxic activity against L1210 leukaemia cells showed that fraction 3 (F3) was the most active fraction with an IC50 of 1.26 µg/mL. Each dose's F3 cytotoxic activity showed that the IC50 7.5 kGy irradiation sample did not change significantly with control (0 kGy) based on ANOVA analysis using SPSS 24 with a 95% confidence level. In comparison, irradiation samples of 10 and 15 kGy showed a change in the IC50 value is significant with the control (0 kGy). These results indicate that gamma irradiation can be used as an alternative for preserving C. caudatus with a maximum dose of 7.5 kGy, so that its anti-cancer properties do not change with those without irradiation.